Antihelminthic Activity of Lophira Lanceolata on Heligmosomoides polygyrus Using an Automated High-Throughput Method. (20th January 2023) - Cédric, Yamssi; Christelle Nadia, Noumedem Anangmo; Sylvain Raoul, Simeni Njonnou; Berinyuy, Samuel; Azizi, Mounvera Abdel; Jemimah Sandra, Tientcheu Noutong; Aboubakar Sidiki, Ngouyamsa Nsapkain; Payne, Vincent Khan
Abstract : Background . There are about 13 parasitic infections that are responsible for significant morbidity and mortality but have not received the attention they deserve; thus, they are now known as "neglected tropical diseases" (NTDs). This study was aimed at evaluating the antihelminthic activities of Lophira lanceolata using an automated high-throughput method. Methods . The antihelminthic activity effect of the extracts against H . polygyrus was determined using an automated high-throughput method. For the egg-hatching test, 100 μ L of embryonated egg suspension (60 eggs) was added to 100 μ L of various concentrations of extracts, levamisole, and 1.5% DMSO in a 96-well round-bottom microtitre plate. After mixing, the 96-well microplate was placed in WMicroTracker and incubated for 24 h at 25°C; the movements were recorded every 30 minutes. The same procedure was used for the larval motility assays, where 100 μ L of L1 or L2 larvae (50 larvae) were put in contact with 100 μ L of various concentrations of extracts. Results . The ovicidal activity (hatching) had an IC50 of 1.4 mg/mL for the ethanol extract. The aqueous and ethanol extracts of L . lanceolata showed larvicidal activity on the L1 larvae with IC50 of 1.85 mg/mL and 2.4 mg/mL, respectively, as well as on the L2 larvae with IC50 values of 1.08 mg/mL and 1.02 mg/mL for the aqueous and ethanol extracts, respectively. These results showed that the aqueous extract exhibited a stronger inhibitory power on the hatching rate of parasites than ethanol extracts, while the contrary effect was observed for the larval motility assays. Conclusion . This study provides scientific data on the use of L . lanceolata by the local population for the treatment of helminthiases. However, in vivo and toxicity tests are necessary to assess its activity and safety.